IMPROVEMENT OF MUSCLE STRENGTH IN ISCHEMIC STROKE PATIENTS WITH PASSIVE RANGE OF MOTION THERAPY: LITERATURE REVIEW - Anggia Astuti; Candra Alif Novyanto; Achlish Abdillah; Syaifuddin Kurnianto (Indonesian Journal of Health Care Management, 2022)
Introduction: Stroke is a disease that occurs due to blockage/disruption of blood flow to the brain, which can cause brain tissue death. Ischemic stroke is caused by a sudden loss of blood to the brain and will cause loss of nerve function to paralysis so that stroke patients experience mobility limitations. To overcome this problem can be done with passive range of motion therapy. Method: the method used in this study is a literature review. The source of the article uses the PubMed and Google Scholar databases. Result: Based on 8 journals obtained and reviewed, the results show that passive range of motion therapy is effective for increasing muscle strength in ischemic stroke patients. This exercise can stimulate muscle, which can increase neuromuscular, muscle and chemical activity. Conclusion: Passive range of motion therapy has benefits for increasing muscle strength. In addition, this therapy can also avoid complications of ischemic stroke due to physical mobility barriers experienced by clients such as limitations of some or all of the range of motion, stiffness, muscle weakness, postural disorders, muscle atrophy, pain, joint contractures that can cause disturbances in activities daily living (ADL).